Prevalence, risk factors, and outcomes of dysphagia after stroke: a systematic review and meta-analysis - Song, Wenjing; Wu, Minmin; Wang, Haoran; Pang, Ruifeng; Zhu, Luwen (Frontiers in Neurology, 2024)
Background Dysphagia is a common complication after stroke, which not only brings adverse outcomes but also greatly affects the quality of life of patients. At present, there is no systematic review or meta-analysis to comprehensively evaluate the epidemiological characteristics of post-stroke dysphagia (PSD). A systematic review of the prevalence, risk factors, and prognosis of PSD is essential. Methods Through 31 December 2022, a comprehensive literature search was performed for observational studies related to PSD. Five databases were retrieved. Random-effects models were used to estimate the pooled prevalence, odds ratio (OR), and 95% CIs. Results A total of 34 studies were included, and the results showed that the overall prevalence of PSD was 46.6% (95% CI, 0.405–0.528). The prevalence of dysphagia in ischemic stroke and hemorrhagic stroke was 43.6% (95% CI 0.370–0.501) and 58.8% (95% CI 0.519–0.654), respectively. The prevalence of PSD in Africa was 49.4% (95% CI, 0.196–0.792), in Asia was 40.1% (95% CI, 0.348–0.454), in Europe was 45.8% (95% CI, 0.327–0.590), in North America was 44.3% (95% CI, 0.370–0.517), in South America was 57.5% (95% CI, 0.441–0.708), and in Oceania was 64.1% (95%CI, 0.558, 0.724). In risk factor analysis, hypertension, previous stroke, and atrial fibrillation were significantly associated with the occurrence of PSD, pooled OR = 1.179 [(95% CI, 1.002–1.386), p < 0.05], pooled OR = 1.514 [(95% CI, 1.204–1.905), p < 0.001], and pooled OR = 1.980 [(95% CI, 1.580–2.481), p < 0.001]. In outcome studies, the prevalence of aphasia and dysarthria in PSD was 35.6% (95% CI, 0.213–0.499) and 54.5% (95% CI, 0.293–0.798), respectively. The prevalence of respiratory tract infection was 27.1% (95%CI, −0.038–0.579), and the prevalence of pneumonitis was 32.1% (95% CI, 0.224–0.418). Persistence of dysphagia at discharge and at 1 month was 74.5% (95% CI, 0.621–0.869) and 50.9% (95% CI, 0.142–0.876), respectively. Mortality rates for PSD patients during admission and discharge at 1 month, 3 months, and 1 year were 11.8% (95% CI, 0.083–0.152), 26.5% (95% CI, 0.170–0.359), 25.7% (95% CI, 0.19–0.324), and 31.3% (95% CI, 0.256–0.369), respectively. Conclusion This study found that the overall prevalence of PSD was 46.6%. Prevalence is most influenced by the diagnosis method. Hypertension, history of stroke, atrial fibrillation, patient age, and stroke severity were risk factors significantly associated with PSD. The prevalence of aphasia, dysarthria, respiratory tract infection, and pneumonitis in PSD patients is 2–4 times that of patients without PSD. Systematic review registration: www.crd.york.ac.uk/PROSPERO, PROSPERO, CRD42021252967.